Analysis of germination characteristics and metabolome of Medicago ruthenica in response to saline-alkali stress - Wei, Xiaoli; Wang, Jie; Xu, Chengti; Zhao, Yuanyuan; Pu, Xiaojian; Wang, Wei; Lu, Guangxin (Frontiers in Plant Science, 2025)
IntroductionThis study aimed to investigate the seed germination characteristics and metabolic response mechanisms of Medicago ruthenica under saline-alkali stress, with the goal of elucidating its physiological and molecular mechanisms of salt-alkali tolerance.MethodsIt was systematically analyzed the germination characteristics of four M. ruthenica germplasm resources (YSZ, XHZ, Shoulu, and Longzhong 1) from different origins with various concentrations of individual salts (NaCl, Na2SO4, NaHCO3) and compound saline-alkali stress treatments. Additionally, the metabolite changes in the domesticated species under saline-alkali stress were examined using metabolomics technology.ResultsThe results indicated that low concentrations of NaCl stress did not significantly inhibit the germination of M. ruthenica seeds; rather, it promoted germination to some extent. In contrast, high concentrations of NaHCO3 and compound saline-alkali stress significantly inhibited both seed germination and seedling growth. The germination characteristics of M. ruthenica germplasm resources from different sources exhibit variability under saline-alkali stress. Domesticated species demonstrated strong tolerance to salt-alkali conditions. Metabolomic analyses indicated that saline-alkali stress significantly impacts key metabolic pathways, including amino acid metabolism, sugar metabolism, and lipid metabolism in M. ruthenica sprouts, with a notable increase in the accumulation of amino acids and their derivatives. Correlation analyses revealed that amino acids such as L-arginine, histidine, and glutamine are significantly positively correlated with germination rate and root length, suggesting that these amino acids play a crucial role in M. ruthenica’s response to saline-alkali stress.DiscussionThis study provided a new theoretical foundation for understanding the salt-alkali tolerance mechanisms of M. ruthenica and serves as an important reference for breeding salt-alkali tolerant forage varieties and for the ecological restoration of saline-alkali land.